2003
DOI: 10.1042/bj20030405
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid transporters: roles in amino acid sensing and signalling in animal cells

Abstract: Amino acid availability regulates cellular physiology by modulating gene expression and signal transduction pathways. However, although the signalling intermediates between nutrient availability and altered gene expression have become increasingly well documented, how eukaryotic cells sense the presence of either a nutritionally rich or deprived medium is still uncertain. From recent studies it appears that the intracellular amino acid pool size is particularly important in regulating translational effectors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
279
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(285 citation statements)
references
References 216 publications
2
279
2
2
Order By: Relevance
“…Signaling effects through amino acid transporters are now a well-established concept in mammalian cell biology (36). Although much remains to be learned about signaling pathways that are affected by SNAT2, the data in Figures 6 and 7 suggest that the level of SNAT2 inhibition by acidosis exerts functionally significant effects on mTOR, consistent with an earlier report of coregulation of SNAT2 and mTOR in L6 cells that were treated with ceramide (17).…”
Section: Snat2 Regulates Mtor and Influences Protein Metabolismsupporting
confidence: 79%
See 2 more Smart Citations
“…Signaling effects through amino acid transporters are now a well-established concept in mammalian cell biology (36). Although much remains to be learned about signaling pathways that are affected by SNAT2, the data in Figures 6 and 7 suggest that the level of SNAT2 inhibition by acidosis exerts functionally significant effects on mTOR, consistent with an earlier report of coregulation of SNAT2 and mTOR in L6 cells that were treated with ceramide (17).…”
Section: Snat2 Regulates Mtor and Influences Protein Metabolismsupporting
confidence: 79%
“…At first glance, this is surprising because a wide range of amino acid transporter genes are expressed in muscle and a number of these transport l-Gln (36). Not all of these, however, directly accumulate l-Gln inside cells against its concentration gradient.…”
Section: Snat2 Determines L-gln Concentration In L6-g8c5 Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Poncet and Taylor (2013), different nutrient transporters have different gene expression patterns and functions. For example, amino acids are transported into the intestinal epithelial cells as di-or tri-peptides by the H + -dependent peptide transporter 1, PepT1 (Leibach and Ganapathy, 1996) or a variety of amino acid transporters that have specificity for anionic, cationic, or neutral amino acids (Hyde et al, 2003). Most of the studies are focused on the gene expressions of intestine nutrient transporters in precocial poultry, such as chicken (Mott et al, 2008;Sun et al, 2015;Miska et al, 2014) and turkey (de Oliveira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the mRNA expression level of cationic amino acid transporter (CAT-1) in the liver is increased by intake of Lys in pigs (39), and three basic amino acids (Lys, Arg, and His) are commonly transported via CAT-1 (40). Additionally, His is reported to suppress lipogenesis-related genes in the mouse liver (41).…”
Section: Discussionmentioning
confidence: 99%